The Implementation of CSR on EFL Students' Reading Class in Different Group Sizes - Ita Moraliawati; Johannes Ananto Prayogo; Gunadi Harry Sulistyo (Pascasarjana Universitas Negeri Malang, 2020)
Abstract: This study addresses senior high school students' reading comprehension on expository texts and its relation with the group sizes assigned to the students. It involves 133 eleventh grade students of SMAN Model Terpadu Bojonegoro. Quantive data were analyzed descriptively. The findings show that CSR affect the students' reading comprehension significantly. Yet, it fails to reveal the effect of group sizes arrangement on the strategies applied towards the students reading comprehension. Consequently, the use of CSR in reading class can not be related to the group sizes assigned to the students.  Abstrak: Penelitian ini bertujuan untuk mengungkap penguasaan pemahaman bacaan siswa SMA dan hubungannya dengan ukuran kelompok yang ditetapkan pada siswa. Penelitian ini melibatkan 133 siswa kelas XI SMAN Model Terpadu Bojonegoro. Data kuantitatif dianalisis secara deskriptif. Hasil penelitian menunjukkan bahwa penggunaan CSR memberikan pengaruh yang signifikan pada pemahaman bacaan siswa. Namun, penelitian ini gagal menunjukkan pengaruh ukuran pengaturan kelompok dalam strategi yang diterapkan terhadap pemahaman bacaan siswa. Karena itu, penggunaan CSR dalam pembelajaran membaca tidak bisa dihubungkan dengan ukuran kelompok yang ditugaskan kepada siswa.